Forming of the meat and fatt productivity of different genotypes of pigs - Бірта, Г. О.; Бургу, Ю. Г. (Scientific Progress & Innovations, 2012)
Fattening and meat productivity of animals is stipulated their genotype and environment. Under act of the inherited qualities and terms of environment development of animals passes differently. On the physiology stages of the development their rates of forming. They largely depend on intensity of exchange of matters in an organism. In influence of genetic and paratypic factors on separate economic-useful signs clear conformity to the law, which is expressed in the following, is traced: what large force of influence of factors, the more so high degree of cooperation of genotype and environment. Correlations of fatty and bone fabrics at the backwall of pigs are determined not only age, reason, size of eventual living mass at completion of fattening, type of fattening, but also by direction their productivity and pedigree work.